Patterns of transposable element variation and clinality in Drosophila. Issue 6 (11th January 2019) - Adrion, Jeffrey R.; Begun, David J.; Hahn, Matthew W.
Abstract: Natural populations often exist in spatially diverse environments and may experience variation in the strength and targets of natural selection across their ranges. Drosophila provides an excellent opportunity to study the effects of spatially varying selection in natural populations, as both Drosophila melanogaster and Drosophila simulans live across a wide range of environments in North America. Here, we characterize patterns of variation in transposable elements (TEs) from six populations of D. melanogaster and nine populations of D. simulans sampled from multiple latitudes across North America. We find a nearly twofold excess of TEs in D. melanogaster relative to D. simulans, with this difference largely driven by TEs segregating at the lowest and highest allele frequencies. We find no effect of latitude on either total TE abundance or average TE allele frequencies in either species. Moreover, we show that, as a class of mutations, the most common patterns of TE variation do not coincide with the sampled latitudinal gradient, nor are they consistent with local adaptation acting on environmental differences found in the most extreme latitudes. We also do not find a cline in ancestry for North American D. melanogaster —for either TEs or single nucleotide polymorphisms—suggesting a limited role for demography in shaping patterns of TE variation. Though we find little evidence for widespread clinality among TEs in Drosophila, this does not necessarily imply a limited role for TEs in adaptation. We discuss the need for improved models of adaptation to large‐scale environmental heterogeneity, and how these might be applied to TEs.